Business Decision for Optimal Location of Traditional Restaurant in Bandung: Value Focused Thinking (VFT) -Analytical Hierarchy Process (AHP) - Kartika Tjendana; Pri Hermawan (Journal of Economics and Business UBS, 2025)
This research examines the location decision-making process for a traditional home-cooked restaurant serving Yogyakarta cuisine in Bandung, driven by changing customer behavior, increased competitive pressure in the culinary sector, and the impending growth of the business. The owner requires a methodical approach to select the optimal location in Greater Bandung. Therefore, this project thesis evaluates three potential locations using a Multi-Criteria Decision Analysis methodology, which incorporates Value-Focused Thinking (VFT) to determine the six location criteria derived directly from the owner's objectives. The methodology employs the Analytic Hierarchy Process (AHP) to assign weights to each criterion and rank the three location options by suitability. A simple spatial analysis based on Christaller’s Central Place Theory assesses the extent of the residential area surrounding each potential location as well as the presence of service centers in proximity. The analysis proceeded as follows: (1) data collection through interviews and site visits, (2) completion of paired-comparison questionnaires, and (3) establishment of consistency and sensitivity checks. The findings indicate that the Taman Kopo Indah Corridor should be the first priority, owing to its extensive residential base, adequate accessibility, and tolerable levels of direct competition. Additionally, this research serves as a practical decision-support tool for small-scale food businesses seeking to establish new locations for expansion, as it demonstrates how Multi-Criteria Decision Analysis and spatial perspectives can be integrated into the context of Indonesian cities.